2011
DOI: 10.2341/10-163-l
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Wetness Effects on Bond Strength Using Different Adhesive Systems

Abstract: The enamel surface should not be desiccated extensively when an all-in-one self-etching adhesive is employed. SUMMARYObjective: To evaluate, through the application of different dentin bonding systems, the influence of wetness on shear bond strength in enamel.Methods: This study evaluated three etch-andrinse adhesive systems (Scotchbond MP [used with and without primer]; Singlebond; and Prime&Bond 2.1) and two self-etching adhesive systems (Clearfil SE Bond; and Xeno IV). Flat bovine enamel surfaces were eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…Furuse et al 25) applied five different adhesive systems including SB2 and CSE and found no statistical difference between μSBS of resin composite to the wet and dry enamel surfaces. Similarly, Chuang et al 26) reported that marginal quality was not affected when SB2 was applied on dry and wet enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Furuse et al 25) applied five different adhesive systems including SB2 and CSE and found no statistical difference between μSBS of resin composite to the wet and dry enamel surfaces. Similarly, Chuang et al 26) reported that marginal quality was not affected when SB2 was applied on dry and wet enamel.…”
Section: Discussionmentioning
confidence: 99%
“…8 In other studies, results have shown that one step self-etch adhesives can produce shear bond strengths to ground enamel that are even higher than those of total-etch adhesive systems. 9,10 In this study, the self-etching systems showed lower bond strengths to enamel compared to a total-etch system. This could be due to less demineralization of enamel by the priming agent compared.…”
Section: Discussionmentioning
confidence: 99%
“…10 The time saving and efficiency of the selfetching primers approach combined is certainly a significant advantage when compared to the many multiple step adhesive systems. Nevertheless, it is questionable whether enamel adhesion tests in vitro are representative of in vivo performance of bonding materials which were believed to be less effective under clinical conditions rather than under laboratory ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fracture patterns in specimens after microshear bond strength test. This work used the in vitro method with bovine incisor teeth selection 14,15 , maintained in formalin 2% during 15 days for disinfection 16 .…”
Section: De Souza Et Al • Journal Of Research In Dentistry 2016mentioning
confidence: 99%